La educación física en la básica primaria (2020)
Introduction: Physical education is seen as a subject related only to movement activities: sports, exercise, recreation, leisure activities. Objective: The presence of a devaluation of the matter from the institutional point of view has been detected by assigning few hours and from the family context that is seen as a waste of time. Methodology: The reality is that this subject has little time load within the curriculum and centralization of the institution to meet objectives in other subjects, produces the devaluation of a subject such as Physical Education. Results: This subject is more than a sports practice or physical exercise since it contributes to the development of individual and collective skills; It also allows consolidating knowledge belonging to other subjects and enables the integral development of the student. Conclusions: The present study will analyze the possible competences and abilities to develop through this subject in addition to establishing strategies to improve the subject within the basic primary and will identify the real contributions that this subject can grant for the integral development of children and Girls attending basic elementary level.